Public Policy Issues in Florida: 2017-18 Constitution Revision Commission (CRC) - Rodney L. Clouser (EDIS)
It is an exciting time in Florida public policy; the once-in-every-two-decades Constitution Revision Commission is in the process of recommending changes to the Florida state constitution. This 4-page fact sheet written by Rodney L. Clouser and published by the UF/IFAS Food and Resource Economics Department describes the process and explains how to get involved, evaluate the proposals for changes to the constitution, and cast an informed vote in November 2018. http://edis.ifas.ufl.edu/fe1035